Migratory pathways to Ireland for start-ups and innovative entrepreneurs - Frank Mc Namara; Emma Quinn (The Economic and Social Research Institute (ESRI), 2020)
This European Migration Network study examines policy and practice relating to non-EEA start-ups and innovative entrepreneurs in Ireland. The study is an in-depth examination of the Start-Up Entrepreneur Programme (STEP) by which start-up founders, innovative entrepreneurs and their families come to Ireland. The report briefly considers the Irish start-up landscape and how policy has developed in relation to the migration of non-EEA entrepreneurs, as well as planned future policy direction in this regard.
Keywords: 330; Unternehmensgründung; Flüchtlinge; Migranten; Innovation; Migrationspolitik; EU-Staaten; Irland